THE ABILITY OF ENGLISH DEPARTMENT STUDENTS’ IN USING ADVERB CLAUSES OF TIME - Antika, Rindilla; Wahyuni, Sri; Melvina, Melvina (TELL - US JOURNAL, 2020)
Adverb clauses of time is oen of gramatical rules which is quite difficult to be mastered. This research aimed to describe students’ ability in using adverb clauses of time for past, present and future time at State University of Padang. This research is descriptive research where the population is third year students’ of English Department in State University of Padang. There are 30 students as the samples which are chosen by using cluster sampling. The instrument of this research is test which consist two types of test; multiple choice and fill in the blank with total number are 75 items. The result shows that students’ ability in using adverb clauses of time is categorized average generally where 50% of the students are able to use adverb clauses of time correctly. Specifically, students’ ability in using adverb of time refers to past time is categorized good with percentage is 74% while students’ ability in using adverb clauses of time refers to present time is categorized low since only 50% students answered correctly. Thus, percentage of students’ ability in using adverb clauses of time refers to future time is categorized low because only 47% students are able to answer the test correctly. In conclusion, students’ ability in using adverb clauses of time is average however, it is suggested to the lecturers to provide more practice about adverb clauses of time.